Análise do controle estatístico da produção para empresa de pequeno porte: um estudo de caso - Indezeichak, Vilmara (2005)
This work aims to analyze a small manufacturing company productive process in order to understand the main improvement difficulties at production process. For this, the concepts of small companies, competitiveness and innovation were reviewed. It was investigated the concepts of Statistical Process Control, as well as the difficulties of implanting it in Small Companies. It was selected a company with serial line production and don’t use any statistical control tool. After choosing the company and the line production, the process production was described. From this description some critical points were identified, and then was applied the attribute control charts and used cause and effect diagram to analyze the detected fails. The results showed that the company is still far from implanting a quality system like Six Sigma, for example. However, using a simple tool like attribute control chart, it was possible to identify the productive process deficiency, showing that its use can reduce waste and rework.